2019
DOI: 10.20944/preprints201901.0141.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upregulation of the Intestinal Paracellular Pathway with Breakdown of Tight and Adherens Junctions in Deficit Schizophrenia

Abstract: In 2001, the first author of this paper reported that schizophrenia is associated with an increased frequency of the haptoglobin (Hp)-2 gene. The precursor of Hp-2 is zonulin, a molecule that affects intercellular tight junction integrity. Recently, we reported increased plasma IgA/IgM responses to Gram-negative bacteria in deficit schizophrenia indicating leaky gut and gut dysbiosis. The current study was performed to examine the integrity of the paracellular (tight and adherens junctions) and transcellular (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…E-Cadherin (epithelial cadherin) is a key component of intestinal adherens junctions, which provide stability and cell-cell adhesion among epithelial cells of the paracellular pathway, modulate intracellular signaling and regulate turnover of the actin cytoskeleton through binding with β-catenin (van Roy and Berx, 2008;Gomez et al, 2015;Bruser and Bogdan, 2017;Hartsock and Nelson, 2008). Interestingly, in our study (Maes et al, 2019) only very modest changes in IgM responses to cytoskeletal proteins, including talin, actin and vinculin were detected in schizophrenia, while the ratio of IgM responses to paracellular versus transcellular proteins was significantly increased in deficit schizophrenia as compared with nondeficit schizophrenia and controls. Actin microfilaments, a major component of the cytoskeleton, maintain the shape and structure of the cell and regulate transcription (Dominguez and Holmes, 2011).…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…E-Cadherin (epithelial cadherin) is a key component of intestinal adherens junctions, which provide stability and cell-cell adhesion among epithelial cells of the paracellular pathway, modulate intracellular signaling and regulate turnover of the actin cytoskeleton through binding with β-catenin (van Roy and Berx, 2008;Gomez et al, 2015;Bruser and Bogdan, 2017;Hartsock and Nelson, 2008). Interestingly, in our study (Maes et al, 2019) only very modest changes in IgM responses to cytoskeletal proteins, including talin, actin and vinculin were detected in schizophrenia, while the ratio of IgM responses to paracellular versus transcellular proteins was significantly increased in deficit schizophrenia as compared with nondeficit schizophrenia and controls. Actin microfilaments, a major component of the cytoskeleton, maintain the shape and structure of the cell and regulate transcription (Dominguez and Holmes, 2011).…”
Section: Introductionmentioning
confidence: 54%
“…Importantly, we reported that the upregulated paracellular leak pathway and increased bacterial translocation coupled with other biomarkers of schizophrenia significantly predicted PHEMN (psychosis, hostility, excitation, mannerism and negative) symptoms, psychomotor retardation, formal thought disorders and neurocognitive impairments, including semantic and episodic memory (Maes et al, 2019). Those biomarkers include: lowered natural IgM to malondialdehyde (MDA), increased levels of CCL-11 or eotaxin, an endogenous cognition deteriorating chemokine (ECDC), increased IgA responses to neurotoxic and excitotoxic tryptophan catabolites (TRYCATs) versus more protective TRYCATs and an index of immune activation based on assays of IL-10, soluble IL-1 receptor antagonist (sIL-1RA) and macrophage inflammatory protein (MIP)-1 (Maes et al, 2019). Based on those results we suggested that breakdown of TJs and AJs and the consequent translocation of Gram-negative bacteria may have induced the above mentioned neuro-immune pathways which all together may cause neuroprogression, namely dysfunctions in synaptic sampling, synaptic plasticity, synaptogenesis, neurogenesis, neuroprotection, etc.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations